2010
DOI: 10.1007/s11671-010-9623-0
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Controlled Defects Inside Colloidal Crystal Arrays with a Focused Ion Beam

Abstract: In this work the reliability of the focused-ion-beam (FIB) patterning on polystyrene (PS) colloidal crystals at different scales is determined. Ordered arrays of PS spheres (465 nm) are successfully modified by selectively removing a single sphere. The water-vapor assisted FIB milling is crucial to obtain this result. Furthermore, isolated PS spheres are FIB drilled with or without chemically enhanced milling aiming at the exploration of the limits of such a technique. These controlled defects created using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Isa and coworkers employed colloidal self‐assembly at liquid‐liquid interfaces to fabricate regular, open particle lithography masks, which can be employed to produce diverse biosensing structures . Magni and coworkers reported that ordered arrays of PS spheres (465 nm) are successfully modified by selectively removing a single sphere focused‐ion beam (FIB) patterning . Complex 3D nanostructures can be fabricated by harnessing the Talbot field distribution generated by a 2D nanosphere array.…”
Section: New Development In Colloidal Lithographymentioning
confidence: 99%
“…Isa and coworkers employed colloidal self‐assembly at liquid‐liquid interfaces to fabricate regular, open particle lithography masks, which can be employed to produce diverse biosensing structures . Magni and coworkers reported that ordered arrays of PS spheres (465 nm) are successfully modified by selectively removing a single sphere focused‐ion beam (FIB) patterning . Complex 3D nanostructures can be fabricated by harnessing the Talbot field distribution generated by a 2D nanosphere array.…”
Section: New Development In Colloidal Lithographymentioning
confidence: 99%
“…Great efforts have been made in the controlled incorporation of articial defects inside the CCs. [13][14][15][16][17][18][19] Two-photon polymerization (TPP) is a versatile topdown method for the controlled insertion of designed defects into a CC with high resolution and precise position, in which the photochemical process is conned to a focal volume of the order of the cube of the excitation wavelength. 20 Rinne et al have created designed defects in an opal CC via TPP, and demonstrated the waveguiding properties aer silicon replication.…”
Section: Introductionmentioning
confidence: 99%